Implementation of Flipbook Based Teaching Materials Pancasila Education Subjects to Improve the Mutual Cooperation Character of Class IV Students at SDN Karah 1 Surabaya - Alfina Ifadah; Nafiah; Aris Budianto (Universitas Nahdatul Ulama Surabaya, 2025)
The rapid development of globalization has brought significant changes to the world. In the current era, many media programs highlight weaknesses and promote negative behaviors, which, if left unchecked, may be easily imitated by children. This situation poses a risk of developing habits that undermine good character. Therefore, schools have an important role in instilling positive values. One such value is the spirit of mutual cooperation, which can be cultivated through the use of flipbook teaching materials in the Pancasila Education subject. This research aims to improve the mutual cooperation character of students by implementing flipbook-based teaching materials in Pancasila Education for Grade IV A students at SDN Karah 1 Surabaya. The research employed Classroom Action Research (PTK) conducted in two cycles. The subjects were Grade IV A students at SDN Karah 1 Surabaya. Data were collected before the intervention (pre-cycle) and after each cycle to measure the improvement in mutual cooperation. Pre-cycle: 28% of students achieved the expected character development, while 72% did not. Cycle I: Improvement to 45% complete and 55% incomplete. Cycle II: Further improvement to 90% complete and only 10% incomplete. These results demonstrate a significant increase, meeting the success indicators set for the study. The use of flipbook teaching materials in Pancasila Education effectively improved the mutual cooperation character of Grade IV A students at SDN Karah 1 Surabaya when implemented in accordance with PTK procedures. It is recommended that educators integrate innovative digital teaching materials, such as flipbooks, to foster positive character values in students, and further research can explore its application in other subjects and grade levels.